Effect of domestic cooking methods on physicochemical, nutritional and sensory properties of different varieties of brown rice from Southern Thailand and Malaysia - Chapagai, M.K.; Wan Rosli, W. I.; Wan Manan, W. M.; Jalil, R. A.; Karrila, T.; Pinkaew, S. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Consumption of brown rice is increasing on account of higher nutritional components such as vitamins, minerals, fibres and antioxidants than white rice. However, the effect of domestic cooking methods on nutritional attributes of brown rice is not well-characterized. Hence, this study aimed to investigate the effect of cooking methods; pressure cooker (PC) and rice cooker (RC) on physicochemical, nutritional and sensory properties of brown rice from five different varieties: Sungyod (SY), Chiang (CH), and Lepnok (LP) of Thai and long grain LS1 and LS2 of Malaysian origin. Peak viscosity (PV) and final viscosity (FV) among uncooked samples were significantly different except for LS1 and LS2. Between cooking methods, protein content (8.17 – 10.14%) was significantly different (p < 0.05) except in SY, LS1 and LS2 varieties whereas fat (1.74 – 2.71%) and ash content (1.15 – 1.46%) showed significant difference (p < 0.05) only in LP and SY varieties. Loss of iron was significantly higher in RC method than PC method but zinc and thiamine was insignificant. The LS1 and LS2 cooked in PC was significantly softer (p < 0.05) than cooked in RC. Hardness of PC cooked rice was correlated with PV (r = –0.965), breakdown viscosity (r = –0.973), setback viscosity (r = –0.944) at p < 0.01 and pasting temperature (r = 0.89, p < 0.05) of uncooked brown rice flours. Overall, PC was found better over RC in terms of cooking time, textural properties, nutrients and sensory attributes.